2020
DOI: 10.1002/wcc.693
|View full text |Cite
|
Sign up to set email alerts
|

Who are American evangelical Protestants and why do they matter forUSclimate policy?

Abstract: White evangelical Protestants are the most skeptical major religious group in the United States regarding climate change. While their position of political influence in the Republican coalition is widely recognised, the full range of effects of this position on evangelicals' climate opinions is not. To move research on evangelicals from the margins of climate change opinion research, we review and integrate the interdisciplinary literature on US evangelicals, climate change, and politics. In assessing this lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 100 publications
(165 reference statements)
1
18
0
Order By: Relevance
“…A significant body of literature from the U.S. shows that environmental and climate concern is particularly low among White evangelical Protestants. There is an ongoing debate about which factors can help explain this finding, specifically whether the resistance to environmental and climate policy among evangelicals can most accurately be explained by reference to political orientation (including values and attitudes towards collective action), religious beliefs, or a combination of both (Veldman et al 2021). A significant number of studies have confirmed that political conservatives tend to be less concerned about the environment than their liberal counterparts (Dunlap et al 2001;Dunlap 2010, 2011;Antonio and Brulle 2011;McCright et al 2014).…”
Section: Climate Science and The Evangelical Communitymentioning
confidence: 99%
See 4 more Smart Citations
“…A significant body of literature from the U.S. shows that environmental and climate concern is particularly low among White evangelical Protestants. There is an ongoing debate about which factors can help explain this finding, specifically whether the resistance to environmental and climate policy among evangelicals can most accurately be explained by reference to political orientation (including values and attitudes towards collective action), religious beliefs, or a combination of both (Veldman et al 2021). A significant number of studies have confirmed that political conservatives tend to be less concerned about the environment than their liberal counterparts (Dunlap et al 2001;Dunlap 2010, 2011;Antonio and Brulle 2011;McCright et al 2014).…”
Section: Climate Science and The Evangelical Communitymentioning
confidence: 99%
“…Although most studies conclude that political orientation is the strongest predictor of climate opposition (see further in Edvardsson Björnberg et al 2017), there is evidence to suggest that religious belief may also shape the environmental attitudes and actions of evangelicals (see Veldman et al 2021 for a discussion). As noted by Veldman et al (2021), there is currently a noticeable lack of qualitative studies investigating some of the possible religious drivers of climate opposition.…”
Section: Climate Science and The Evangelical Communitymentioning
confidence: 99%
See 3 more Smart Citations